2019
DOI: 10.33808/marusbed.546903
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Nursing Students: The Effect of Academic Stress and Social Support

Abstract: Objective: This study was conducted to evaluate the levels of psychological resilience, academic stress and social support available to nursing students and the relationship between these factors. Methods: The population of the study, which had a descriptive and correlational research design, was made up of 1202 students, while the sample consisted of 322 students selected using the sample size formula for a known population. Data were collected using a Structured Questionnaire, the Psychological Resilience Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
0
23
1
2
Order By: Relevance
“…In this study, the total NESS score average of the students was moderate. These findings were lower than the NESS mean scores obtained from the other studies conducted in Turkey (Bahadır -Yılmaz, 2016;Karabulutlu et al, 2019;Küçükakça et al, 2017;Ozsaban et al, 2019;Tarsuslu et al, 2020;Yıldırım et al, 2016). In accordance with the findings of these studies, students reported that they were not supported in clinical settings (Dinmohammadi et al, 2014).…”
Section: Discussioncontrasting
confidence: 60%
“…In this study, the total NESS score average of the students was moderate. These findings were lower than the NESS mean scores obtained from the other studies conducted in Turkey (Bahadır -Yılmaz, 2016;Karabulutlu et al, 2019;Küçükakça et al, 2017;Ozsaban et al, 2019;Tarsuslu et al, 2020;Yıldırım et al, 2016). In accordance with the findings of these studies, students reported that they were not supported in clinical settings (Dinmohammadi et al, 2014).…”
Section: Discussioncontrasting
confidence: 60%
“…Literatüre bakıldığında öğrenciler için sadece akademik alanın değil, klinik uygulama ortamının da büyük stres kaynağı olduğu görülmektedir (Gibbons ve ark., 2011;Jimenez ve ark., 2010). Araştırmamızda öğrencilerin HESÖ toplam puan ortalaması (66,76±16,56) olup, HESÖ kullanılarak gerçekleştirilen çalışmalara göre yüksek bulunmuştur (Ergin, Çevik ve Pakiş Çetin, 2018;Çakar, Yıldırım Şişman ve Oruç, 2019;Ozsaban, Turan ve Kaya, 2019). Buna göre araştırmamız örneklemindeki hemşirelik öğrencilerinin, orta düzeyde hemşirelik eğitim stresi deneyimledikleri söylenebilir.…”
Section: Discussionunclassified
“…Having limited knowledge about COVID-19 can cause further anxiety and fear [23]. Stress may impact concentration, memory, and decision making and problem-solving skills [24]. Stress has an impact on the students' academic achievement [10], [24], [25] and may result in physical complaints, and behavioural problems [10], [24].…”
Section: Figure 1 Perceived Stress and Resilience Of Nursing Undergra...mentioning
confidence: 99%